1966
DOI: 10.1136/bjo.50.12.740
|View full text |Cite
|
Sign up to set email alerts
|

Foveal electroretinogram as a clinical test.

Abstract: THE electroretinogram (ERG) is used as an objective test of retinal function. However, in normal clinical recording, the potential investigated is produced by the entire retina (Asher, 1951). Therefore, though diffuse retinal damage can be detected, normal responses are obtained if the lesion is small and localized, such as a macular degeneration.It has been shown in animal experiments that local ERGs can be obtained by using micro-electrodes (Brown and Wiesel, 1959). More recently local responses have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Several studies have shown that a small field macular ERG can be recorded providing that the surrounding retina is light-adapted in order to minimize the effects of stray-light (Arden and Bankes, 1966;Van Lith and Henkes, 1968;Sandberg et al, 1977). This ERG, unlike the full field flash ERG, is substantially reduced in retinal diseases affecting the foveo-macular region (Jacobson et al, 1979;Sandberg et al, 1980;Vaegan and Billson, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that a small field macular ERG can be recorded providing that the surrounding retina is light-adapted in order to minimize the effects of stray-light (Arden and Bankes, 1966;Van Lith and Henkes, 1968;Sandberg et al, 1977). This ERG, unlike the full field flash ERG, is substantially reduced in retinal diseases affecting the foveo-macular region (Jacobson et al, 1979;Sandberg et al, 1980;Vaegan and Billson, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Two early reports demonstrated that focal ERGs limited to the fovea could be recorded from ophthalmic patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the ffERG, the focal ERG (fERG) has the ability to specifically stimulate the fovea-useful when evaluating macular disease [22,23]. A flickering light stimulus is utilised to stimulate the macular region and measures macular cone photoreceptor and bipolar cell function [24].…”
Section: Focal Ergmentioning
confidence: 99%